Crop rotation phase has a greater impact on soil biology than crop rotation diversity - Marijke Struijk; Erika Degani; Samuel G. Leigh; Emma Bowen; Sion Thomas; Simon R. Mortimer; Andrew P. Whitmore; Frank Ashwood; Suzanne J. Clark; Tom Sizmur (Agriculture, Ecosystems & Environment, 2026)

Artificial barriers and estuarine squeeze: A novel assessment of estuarine vulnerability to climate change and sea level rise - Helen Pietkiewicz; Robert J.G. Mortimer; Andrew G. Hirst; Jonathan P. Lewis; Lucy Clarke; Sally Little (Estuarine, Coastal and Shelf Science, 2025)

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Absence of a home-field advantage within a short-rotation arable cropping system - Marijke Struijk; Andrew P. Whitmore; Simon Mortimer; Xin Shu; Tom Sizmur (Plant and Soil, 2023)
Aims The home-field advantage (HFA) hypothesis predicts faster decomposition of plant residues in home soil compared to soils with different plants ( away ), and has been demonstrated in forest and grassland ecosystems. It remains unclear if this legacy effect applies to crop residue decomposition in arable crop rotations. Such knowledge could improve our understanding of decomposition dynamics in arable soils and may allow optimisation of crop residue amendments in arable systems by cleverly combining crop-residue rotations with crop rotations to increase the amount of residue-derived C persisting in soil. Methods We tested the HFA hypothesis in a reciprocal transplant experiment with mesh bags containing wheat and oilseed rape residues in soils at three stages of a short-rotation cropping system. Subsets of mesh bags were retrieved monthly for six months to determine residue decomposition rates, concomitantly measuring soil available N, microbial community structure (phospholipid fatty acid analysis), and microbial activity (Tea Bag Index protocol) to assess how plants may influence litter decomposition rates via alterations to soil biochemical properties and microbial communities. Results The residues decomposed at similar rates at all rotational stages. Thorough data investigation using several statistical approaches revealed no HFA within the crop rotation. Soil microbial community structures were similar at all rotational stages. Conclusions We attribute the absence of an HFA to the shortness of the rotation and soil disturbance involved in intensive agricultural practices. It is therefore unlikely that appreciable benefits could be obtained in short conventionally managed arable rotations by introducing a crop-residue rotation.

Global patterns in endemicity and vulnerability of soil fungi - Leho Tedersoo; Vladimir Mikryukov; Alexander Zizka; Mohammad Bahram; Niloufar Hagh‐Doust; Sten Anslan; Oleh Prylutskyi; Manuel Delgado‐Baquerizo; Fernando T. Maestre; Jaan Pärn; Maarja Öpik; Mari Moora; et al. (Global Change Biology, 2022)
Fungi are highly diverse organisms, which provide multiple ecosystem services. However, compared with charismatic animals and plants, the distribution patterns and conservation needs of fungi have been little explored. Here, we examined endemicity patterns, global change vulnerability and conservation priority areas for functional groups of soil fungi based on six global surveys using a high‐resolution, long‐read metabarcoding approach. We found that the endemicity of all fungi and most functional groups peaks in tropical habitats, including Amazonia, Yucatan, West‐Central Africa, Sri Lanka, and New Caledonia, with a negligible island effect compared with plants and animals. We also found that fungi are predominantly vulnerable to drought, heat and land‐cover change, particularly in dry tropical regions with high human population density. Fungal conservation areas of highest priority include herbaceous wetlands, tropical forests, and woodlands. We stress that more attention should be focused on the conservation of fungi, especially root symbiotic arbuscular mycorrhizal and ectomycorrhizal fungi in tropical regions as well as unicellular early‐diverging groups and macrofungi in general. Given the low overlap between the endemicity of fungi and macroorganisms, but high conservation needs in both groups, detailed analyses on distribution and conservation requirements are warranted for other microorganisms and soil organisms.

The Norfolk Ridge seamounts: Eocene–Miocene volcanoes near Zealandia’s rifted continental margin - N. Mortimer; M. Patriat; P. B. Gans; A. Agranier; G. Chazot; J. Collot; M. P. Crundwell; P. M. J. Durance; H. J. Campbell; S. Etienne (Australian Journal of Earth Sciences, 2021)

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Many unreported crop pests and pathogens are probably already present - Daniel P. Bebber; Elsa Field; Heng Gui; Peter Mortimer; Timothy Holmes; Sarah J. Gurr (Global Change Biology, 2019)
Invasive species threaten global biodiversity, food security and ecosystem function. Such incursions present challenges to agriculture where invasive species cause significant crop damage and require major economic investment to control production losses. Pest risk analysis (PRA) is key to prioritize agricultural biosecurity efforts, but is hampered by incomplete knowledge of current crop pest and pathogen distributions. Here, we develop predictive models of current pest distributions and test these models using new observations at subnational resolution. We apply generalized linear models (GLM) to estimate presence probabilities for 1,739 crop pests in the CABI pest distribution database. We test model predictions for 100 unobserved pest occurrences in the People's Republic of China (PRC), against observations of these pests abstracted from the Chinese literature. This resource has hitherto been omitted from databases on global pest distributions. Finally, we predict occurrences of all unobserved pests globally. Presence probability increases with host presence, presence in neighbouring regions, per capita GDP and global prevalence. Presence probability decreases with mean distance from coast and known host number per pest. The models are good predictors of pest presence in provinces of the PRC, with area under the ROC curve (AUC) values of 0.75–0.76. Large numbers of currently unobserved, but probably present pests (defined here as unreported pests with a predicted presence probability >0.75), are predicted in China, India, southern Brazil and some countries of the former USSR. We show that GLMs can predict presences of pseudoabsent pests at subnational resolution. The Chinese literature has been largely inaccessible to Western academia but contains important information that can support PRA. Prior studies have often assumed that unreported pests in a global distribution database represent a true absence. Our analysis provides a method for quantifying pseudoabsences to enable improved PRA and species distribution modelling.

Enhancing Soil Organic Matter as a Route to the Ecological Intensification of European Arable Systems - M. P. D. Garratt; R. Bommarco; D. Kleijn; E. Martin; S. R. Mortimer; S. Redlich; D. Senapathi; I. Steffan-Dewenter; S. Świtek; V. Takács; S. van Gils; W. H. van der Putten; et al. (Ecosystems, 2018)

Leaching of copper and nickel in soil-water systems contaminated by bauxite residue (red mud) from Ajka, Hungary: the importance of soil organic matter - Cindy L. Lockwood; Douglas I. Stewart; Robert J. G. Mortimer; William M. Mayes; Adam P. Jarvis; Katalin Gruiz; Ian T. Burke (Environmental Science and Pollution Research, 2015)

Intensive agriculture reduces soil biodiversity across Europe - Maria A. Tsiafouli; Elisa Thébault; Stefanos P. Sgardelis; Peter C. de Ruiter; Wim H. van der Putten; Klaus Birkhofer; Lia Hemerik; Franciska T. de Vries; Richard D. Bardgett; Mark Vincent Brady; Lisa Bjornlund; Helene Bracht Jørgensen; et al. (Global Change Biology, 2015)
Soil biodiversity plays a key role in regulating the processes that underpin the delivery of ecosystem goods and services in terrestrial ecosystems. Agricultural intensification is known to change the diversity of individual groups of soil biota, but less is known about how intensification affects biodiversity of the soil food web as a whole, and whether or not these effects may be generalized across regions. We examined biodiversity in soil food webs from grasslands, extensive, and intensive rotations in four agricultural regions across Europe: in Sweden, the UK , the Czech Republic and Greece. Effects of land‐use intensity were quantified based on structure and diversity among functional groups in the soil food web, as well as on community‐weighted mean body mass of soil fauna. We also elucidate land‐use intensity effects on diversity of taxonomic units within taxonomic groups of soil fauna. We found that between regions soil food web diversity measures were variable, but that increasing land‐use intensity caused highly consistent responses. In particular, land‐use intensification reduced the complexity in the soil food webs, as well as the community‐weighted mean body mass of soil fauna. In all regions across Europe, species richness of earthworms, Collembolans, and oribatid mites was negatively affected by increased land‐use intensity. The taxonomic distinctness, which is a measure of taxonomic relatedness of species in a community that is independent of species richness, was also reduced by land‐use intensification. We conclude that intensive agriculture reduces soil biodiversity, making soil food webs less diverse and composed of smaller bodied organisms. Land‐use intensification results in fewer functional groups of soil biota with fewer and taxonomically more closely related species. We discuss how these changes in soil biodiversity due to land‐use intensification may threaten the functioning of soil in agricultural production systems.

Urban and agricultural soils: conflicts and trade-offs in the optimization of ecosystem services - H. Setälä; R. D. Bardgett; K. Birkhofer; M. Brady; L. Byrne; P. C. de Ruiter; F. T. de Vries; C. Gardi; K. Hedlund; L. Hemerik; S. Hotes; M. Liiri; et al. (Urban Ecosystems, 2014)

Gypsum addition to soils contaminated by red mud: implications for aluminium, arsenic, molybdenum and vanadium solubility - Alizée P. Lehoux; Cindy L. Lockwood; William M. Mayes; Douglas I. Stewart; Robert J. G. Mortimer; Katalin Gruiz; Ian T. Burke (Environmental Geochemistry and Health, 2013)

Paleocene MORB and OIB from the Resolution Ridge, Tasman Sea - N. Mortimer; P. B. Gans; F. Hauff; D. H. N. Barker (Australian Journal of Earth Sciences, 2012)

Forest Carbon Offsets and Environmental Benefits: An Argument for Consistent Domestic Policymaking - Michael J. Mortimer; Robert W. Malmsheimer; Stephen P. Prisley (Journal of Forestry, 2011)

Evaluating the role of environmental quality in the sustainable rural economic development of England - J. R. Park; M. J. Stabler; P. J. Jones; S. R. Mortimer; J. R. Tiffin; R. B. Tranter (Environment, Development and Sustainability, 2009)

Seismic stratigraphy and structure of the Northland Plateau and the development of the Vening Meinesz transform margin, SW Pacific Ocean - R. H. Herzer; B. W. Davy; N. Mortimer; P. G. Quilty; G. C. H. Chaproniere; C. M. Jones; A. J. Crawford; C. J. Hollis (Marine Geophysical Research, 2009)

Analysis of the coding regions of VEGFR3 and VEGFC in Milroy disease and other primary lymphoedemas - F. C. Connell; P. Ostergaard; C. Carver; G. Brice; N. Williams; S. Mansour; P. S. Mortimer; Steve Jeffery (Human Genetics, 2009)

Analysis of the coding regions of VEGFR3 and VEGFC in Milroy disease and other primary lymphoedemas - F. C. Connell; P. Ostergaard; C. Carver; G. Brice; N. Williams; S. Mansour; P. S. Mortimer; Steve Jeffery (Human Genetics, 2009)

Projections from the entorhinal cortex, perirhinal cortex, presubiculum, and parasubiculum to the medial thalamus in macaque monkeys: identifying different pathways using disconnection techniques - Richard C. Saunders; Mortimer Mishkin; John P. Aggleton (Experimental Brain Research, 2005)

Mycorrhizal C costs and nutritional benefits in developing grapevines - P. E. Mortimer; E. Archer; A. J. Valentine (Mycorrhiza, 2005)

Construction and characterisation of a hexaploid wheat (Triticum aestivum L.) BAC library from the reference germplasm ‘Chinese Spring’ - S. Allouis; G. Moore; A. Bellec; R. Sharp; P. Faivre Rampant; K. Mortimer; S. Pateyron; T. N. Foote; S. Griffiths; M. Caboche; B. Chalhoub (Cereal Research Communications, 2003)

Analysis of lymphoedema-distichiasis families forFOXC2 mutations reveals small insertions and deletions throughout the gene - R. Bell; G. Brice; A. Child; V. Murday; S. Mansour; C. Sandy; J. Collin; A. Brady; D. Callen; K. Burnand; P. Mortimer; S. Jeffery (Human Genetics, 2001)

Plant species diversity as a driver of early succession in abandoned fields: a multi-site approach - W. H. Van der Putten; S. R. Mortimer; K. Hedlund; C. Van Dijk; V. K. Brown; J. Lepä; C. Rodriguez-Barrueco; J. Roy; T. A. Diaz Len; D. Gormsen; G. W. Korthals; S. Lavorel; et al. (Oecologia, 2000)

Unidirectional polar growth of cells of Seliberia stellata and aquatic seliberia-like bacteria revealed by immunoferritin labeling - Jean M. Schmidt; Mortimer P. Starr (Archives of Microbiology, 1984)

Controlled prehension and release in the C5 quadriplegic elicited by functional electrical stimulation of the paralyzed forearm musculature - P. H. Peckham; J. T. Mortimer; E. B. Marsolais (Annals of Biomedical Engineering, 1980)

Chemotaxonomic significance of the xanthomonadins, novel brominated aryl-polyene pigments produced by bacteria of the genus Xanthomonas - Mortimer P. Starr; Christie L. Jenkins; Lee B. Bussey; Arthur G. Andrewes (Archives of Microbiology, 1977)

Alterations in the cell wall of Spirillum serpens VHL early in its association with Bdellovibrio bacteriovorus 109D - James E. Snellen; Mortimer P. Starr (Archives of Microbiology, 1976)

The choice of pulse duration for chronic electrical stimulation via surface, nerve, and intramuscular electrodes - Patrick E. Crago; P. Hunter Peckham; J. Thomas Mortimer; Joseph P. Van Der Meulen (Annals of Biomedical Engineering, 1974)

Ultrastructural aspects of localized membrane damage in Spirillum serpens VHL early in its association with Bdellovibrio bacteriovorus 109D - James E. Snellen; Mortimer P. Starr (Archives of Microbiology, 1974)

Possible enzymatic bases of bacteriolysis by bdellovibrios - Jay C. -C. Huang; Mortimer P. Starr (Archives of Microbiology, 1973)

Effects of microscope illumination on bacterial development - Daisy A. Kuhn; Mortimer P. Starr (Archives of Microbiology, 1970)

The intracellular blue pigment of Pseudomonas lemonnieri - Mortimer P. Starr; Hans-Joachim Knackmuss; Gladys Cosens (Archives of Microbiology, 1967)

Clonal morphogenesis of Lampropedia hyalina - Daisy A. Kuhn; Mortimer P. Starr (Archives of Microbiology, 1965)

Indigoidine and other bacterial pigments related to 3,3?-bipyridyl - Richard Kuhn; Mortimer P. Starr; Daisy A. Kuhn; Helmut Bauer; Hans-Joachim Knackmuss (Archives of Microbiology, 1965)

On the origin of V-forms in arthrobacter atrocyaneus - Mortimer P. Starr; Daisy A. Kuhn (Archives of Microbiology, 1962)

Arthrobacter atrocyaneus, n. sp., and its blue pigment - Daisy A. Kuhn; Mortimer P. Starr (Archives of Microbiology, 1960)

The blue pigment of Corynebacterium insidiosum - Mortimer P. Starr (Archives of Microbiology, 1958)